2019
DOI: 10.1038/s41598-019-41456-y
|View full text |Cite
|
Sign up to set email alerts
|

Arctic warming interrupts the Transpolar Drift and affects long-range transport of sea ice and ice-rafted matter

Abstract: Sea ice is an important transport vehicle for gaseous, dissolved and particulate matter in the Arctic Ocean. Due to the recently observed acceleration in sea ice drift, it has been assumed that more matter is advected by the Transpolar Drift from shallow shelf waters to the central Arctic Ocean and beyond. However, this study provides first evidence that intensified melt in the marginal zones of the Arctic Ocean interrupts the transarctic conveyor belt and has led to a reduction of the survival rates of sea ic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
150
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 123 publications
(158 citation statements)
references
References 55 publications
8
150
0
Order By: Relevance
“…A follow‐up data set that extends this record using AMSR2 data is currently under development. As could be shown in this study, previously observed positive trends in IP (Preußer et al, ) on the Siberian shelf seas are also found in the 16‐year data set, which underlines an apparent change in polynya dynamics in the Eastern Arctic and, connected to that, changing Transpolar Drift characteristics (Krumpen et al, ).…”
Section: Discussionsupporting
confidence: 87%
“…A follow‐up data set that extends this record using AMSR2 data is currently under development. As could be shown in this study, previously observed positive trends in IP (Preußer et al, ) on the Siberian shelf seas are also found in the 16‐year data set, which underlines an apparent change in polynya dynamics in the Eastern Arctic and, connected to that, changing Transpolar Drift characteristics (Krumpen et al, ).…”
Section: Discussionsupporting
confidence: 87%
“…Ice transport along long‐distance pathways are predicted to diminish in favor of ice exchange between neighboring EEZs by the end of the 21st century under the high emissions scenario, specifically shifting to the EEZs downstream of each EEZ of formation. This is the result of a projected lengthening of the melt season, which decreases average transit times to less than 1 yr for the CESM‐LE, continuing the trend recently reported by Krumpen et al () and Newton et al (). In fact, the CESM‐LE shows a decrease in the fraction of transnational ice exchange between the periods of 2031–2050 and 2081–2100, whereas the CESM‐LW continues to see an increase.…”
Section: Discussionsupporting
confidence: 84%
“…Mobile sea ice floes in the Arctic Ocean are capable of entrapping contaminants along their drift pathways and playing a role in the redistribution of contaminants due to their eventual release upon melting of the ice 2,16,19 . Estimating backward sea ice trajectories is an important tool that facilitates an examination of sea ice sources, drift pathways, thickness changes and atmospheric processes acting on the ice cover 2,[28][29][30] . When utilized in microplastic studies, backward sea ice trajectory data (i.e.…”
mentioning
confidence: 99%